Alterações mamárias – diagnóstico clínico e diferencial: Breast alterations – clinical and differential diagnosis - Pinho Ribeiro, Paulo César (Adolescência e Saúde, 2010)
It is of great importance to the medical professionals, especially pediatricians and gynecologists, the understanding and how to conduct, facilitating the clinic and precise diagnosis, of the breast alterations that can be presented by adolescents. We point in these alterations the worry of the female teenagers with the development of the breasts and of the male teenagers in relation of puberty gynecomastia.